RISK ASSESSMENT AND MANAGEMENT IN ACCOUNTING AND AUDITING - Elena P. Zhuravleva; Natalia P. Adintsova (Вестник Северо-Кавказского федерального университета)
Consider the effect of the factors of financial and economic environment of the organization on the occurrence, classification, information technology management processes and methods for assessing risks in accounting and auditing. Proposed content and sequence of procedures for risk assessment in accounting.